Comparison of Stress, Anxiety, and Depression Levels in Nurses in Specialized and General Ward - Mahdi Khani; Fazlollah Ahmadi; AliAkbar Rasekhi; Yousef Mohammadpour (Iranian Journal of Nursing and Midwifery Research)
Background: Nurses are exposed to higher stress, anxiety, and depression due to the nature of their work. Considering the differences between specialized and general hospital units, this article focuses on comparing the levels of stress, anxiety, and depression among nurses in these two types of units. Materials and Methods: This descriptive-analytical study was conducted in 2023 on 135 nurses in specialized units and 219 nurses in general units selected through stratified random sampling out of 1681 nurses. For this study, 6 public hospitals in the West Azerbaijan province of Iran were selected. Data were collected through a demographic questionnaire and the Depression, Anxiety, Stress Scales-21 (DASS-21) and analyzed using SPSS software. A significance level of 0.05 was considered for this study. Results: This study reported that stress, anxiety, and depression affected 72.04%, 46.33%, and 53.68% of nurses, respectively, with mild to extremely-severe intensity levels. No significant differences were observed in stress, anxiety, and depression between specialized and general units (p > 0.05). Among specialized units (ICU, CCU, and dialysis ward), dialysis unit nurses had significantly lower depression scores (p < 0.05). Additionally, a significant correlation existed between demographic variables and DASS-21 constructs (p > 0.05). Conclusions: The similarities among nurses in specialized and general units outweigh the observed differences. Given the high prevalence of stress, anxiety, and depression among nurses and the negative correlation with job satisfaction, managers should improve job satisfaction to support nurses’ mental health.